The Competitive Intelligence Analysis of Indonesian National Resilience in the Competition of Alternative Energy Resources - AA Oka Wirayudha; Abdul Rivai Ras (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Mastery of energy resources cannot be separated from the state's efforts to strengthen its defense. The shift in the use of fossil energy into alternative and renewable energy sources has created new competition between countries in the world. Again the US has an important role in the competition, but this time the main competitor is the PRC. Using a qualitative approach with a literature study method, this paper tries to provide an analysis from the point of view of competitive intelligence in looking at the context of great power competition on the issue of mastery of alternative energy resources, as well as its impact on Indonesia's position as a country that has a wealth of energy resources. The results of the discussion show that the shift in energy use in the future is strongly influenced by the issue of climate change, investment factors from developed countries in the development of alternative energy resource technologies and industrial factors that have begun to prioritize the use of resources other than fossils. Competition or competition between the US and China will still determine the continuity of alternative energy development in the future. Meanwhile, Indonesia as a country that has reserves of resources needed in the development of new energy will play a strategic role in the competition for mastery of energy resources, especially electricity.